The Effect of Trunk Core Stability Training and Total-Body Resistance Exercise (TRX) on the Performance, Balance, and Strength of Athletes with Ankle Sprain: A Clinical Randomized Trial Study - Fatemeh Hozhabrpour-Fereydani; Farzaneh Taghian; Mohamad Saleki (Vesnu Publications, 2019)
Introduction: Ankle sprain is one of the common injuries among athletes, and is associated with imbalance. Therefore, the purpose of the present study was to compare the effect of trunk core stability training and total-body resistance exercise (TRX) on the performance, balance, and strength of athletes with ankle sprain. Materials and Methods: 40 women athletes with ankle sprain (age: 24.02 ± 2.99 years and weight: 58.52 ± 4.08 kg) were randomly divided into four equal groups including trunk core stability training, TRX, combined training (core stability training + TRX), and control. Experimental groups were trained for eight weeks and 3 sessions/week. The balance, performance, and strength of the subjects before and after the exercises were evaluated using balance (Stork balance stand test and Y test), performance (side-hop test and figure-of-8 hop test), and strength (isokinetic machine) tests. One-way ANOVA and Bonferroni post hoc test were used for data analysis at the significance level of P < 0.05. Results: All three training models resulted in improvement of performance as well as static and dynamic balance compared to the control group (P < 0.001). Moreover, there was a significant difference between the two groups of combined and trunk core stability training in performance, and dynamic and static balance, and also between the TRX and trunk core stability training groups in static balance (P = 0.014). However, only combined training resulted in increased muscle strength in athletes (P = 0.001), and there was no significant difference between the other groups (P < 0.001). Conclusion: All three training models lead to improved performance and static and dynamic balance in athletes with ankle sprain. However, it seems that the combined training (core stability training + TRX) has more significant effects on improvement of balance, performance, and muscle strength in these athletes.